The effect of omega-3 fatty acids and its combination with statins on lipid profile in patients with hypertriglyceridemia: A systematic review and meta-analysis of randomized controlled trials - Yang, Yunjiao; Deng, Wen; Wang, Yanmei; Li, Tongyi; Chen, Yiding; Long, Cong; Wen, Qing; Wu, Yue; Chen, Qiu (Frontiers in Nutrition, 2022)
Background/Aims: Omega-3 fatty acids (OM3-FA), a promising treatment for high triglycerides, have gradually attracted public attention. However, some studies showed that their application presented tricky problems, like increasing LDL-C levels. This study aimed to systematically evaluate the effect of OM3-FA or their combination with statins on the lipid profile in patients with hypertriglyceridemia. Materials and Methods: This study followed the preferred reporting items for systematic reviews and meta-analyses (PRISMA 2020) guidelines. PubMed, Embase, Web of science, and Cochrane library were searched up to May 15, 2022. The random-effects model was applied to calculate the mean difference (MD) and associated 95% confidence intervals (CI). Results: This meta-analysis included 32 studies with 15903 subjects. When OM3-FA was used as monotherapy compared with placebo, it significantly decreased TG (MD: -39.81, 95%CI: -54.94 to -24.69; P<0.001), TC (MD: -2.98, 95%CI -5.72 to -0.25, p= 0.03), VLDL-C (MD: -25.12, 95%CI: -37.09 to -13.14; p<0.001), and non-HDL-C levels (MD: -5.42, 95%CI: -8.06 to-2.78; p<0.001), and greatly increased LDL-C (MD: 9.10, 95%CI: 4.27 to 13.94; p<0.001) and HDL levels (MD: 1.60, 95%CI: 0.06 to 3.15; p=0.04). Regarding Apo-B and Apo-AI, no significant effect was identified. When OM3-FA was combined with statins, significant reductions were observed in the concentrations of TG (MD: -29.63, 95%CI -36.24 to -23.02; P<0.001), TC (MD: -6.87, 95%CI: -9.30 to -4.45, p<0.001), VLDL-C (-21.13, 95%CI: -24.76 to -15.50; p<0.001), non-HDL-C (MD: -8.71, 95%CI: -11.45 to -5.98; p<0.001), Apo-B (MD: -3.50, 95%CI: -5.37 to-1.64; p<0.001) and Apo-AI (MD: -2.01, 95%CI: -3.07 to -0.95; p<0.001). However, the combined therapy did not exert significant changes on the levels of HDL-C and LDL-C compared to control group. Conclusions: The use of OM3-FA either as monotherapy or in combination with statins may potentially reduce the levels of TG, TC, VLDL-C, non-HDL-C, Apo-B, and Apo-AI while increasing the levels of LDL-C and HDL-C. Nevertheless, the effects of OM3-FA observed in this review should be interpreted with caution due to the high heterogeneity between the included studies.